Karawitan analytical study: sekar-gending “Sungsang” as the jejer ngawitan in Sundanese wayang golek purwa performances - Marsel Ridky Maulana; Uus Karwati (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
Gending “Sungsang” is one of the gending sekar ageng commonly performed in Sundanese wayang golek purwa productions. It is typically presented at the beginning of the performance, earning its designation as gending jejer ngawitan. This study aims to examine the presentational form of gending “Sungsang” within the wayang golek purwa context, while also analyzing its musical composition and its functional role within the overall dramaturgical structure of the performance. The research employs a qualitative approach using content analysis. The findings reveal that gending “Sungsang” demonstrates notable flexibility in its structural presentation. Its distinctiveness lies in its two-goongan structure, which has long served as a defining characteristic of this piece. Initially, the gending functioned exclusively as an accompaniment for murwa or the dalang’s haleuang. However, its usage has since expanded, and it is now also performed to accompany wayang dance or ibingan. Consequently, gending “Sungsang” fulfills multiple functions as a gending jejer ngawitan, acting as the musical prelude to the performance, the accompaniment for the movement of the kayon/gunungan, the dance sequences, and the dalang’s murwa. These variations in presentation enrich the artistic landscape of Sundanese padalangan. Therefore, it is essential for artists and scholars to continue exploring this gending through research that further investigates its specific musical and performative dimensions.